Copper and copper alloys - Davis, J. R. (ASM International, 2001)
Annotation Reviews the engineering aspects of copper and copper alloys. Divided into four sections, the book presents the metallurgy and applications of wrought, cast, and powder alloys; fabrication and finishing procedures; metallography, microstructures, and phase diagrams; and engineering properties and service characteristics. Topics of the 33 articles include heat treatment, copper as a coating, forging and extrusion, welding, micrographs that illustrate the effects of processing, corrosion behavior, fatigue properties, mechanical properties, and electrical conductivity. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Keywords: Copper -- Handbooks, manuals, etc.; Copper alloys -- Handbooks, manuals, etc.; elektronické knihy; electronic books